Examination of Nuclear Receptor Expression in Osteoblasts Reveals Rorβ as an Important Regulator of Osteogenesis - Roforth, Matthew M. (2012)
A complex network of transcription factors contributes to the establishment and maintenance of the osteoblastic phenotype. Although relatively few transcription factors, such as Runx2 and osterix, are essential to the process of osteoblastic differentiation, others serve the purpose of fine-tuning in response to various environmental and hormonal cues. The nuclear receptor (NR) superfamily of transcription factors are involved in numerous aspects of bone biology. In this study, we characterized the expression pattern of the entire NR superfamily in differentiating primary murine calvarial cells in order to identify novel NR regulatory patterns. Dynamic patterns of NR expression were observed throughout the differentiation process. Interestingly, retinoic acid receptor-related orphan receptor β(Rorβ) expression was markedly suppressed at later stages of differentiation. To gain further insight into the function of NRs in bone biology, the NR superfamily was also profiled in mouse bone marrow precursor cells isolated from either young (6 month) or aging, osteoporotic (18–22 month) mice. Of interest, Rorβ was potently overexpressed in the aged cohort. Collectively, these data provided evidence that Rorβ expression is inversely correlated with osteogenic potential, suggesting Rorβ may be an important and unexplored regulator of osteogenesis. To validate this hypothesis, a cell model stably expressing Rorβ in mouse osteoblastic MC3T3-E1 cells was produced (MC3T3-Rorβ). These cells displayed markedly suppressed bone nodule formation as well as reduced osteocalcin and osterix gene expression. Since these genes are Runx2 targets, we reasoned that Rorβ may interfere with Runx2 activity. Consistent with this, transient transfection analysis demonstrated that Rorβ inhibited Runx2-dependent activation of a Runx2-reporter construct. In summary, our data provide a comprehensive profile of NR expression during osteoblast differentiation and identify Rorβ as a novel regulator of osteogenesis and potentially of age-related bone loss through antagonism of Runx2 activity.